Durability of high volume fly ash concrete - Camões, Aires (2006)
It is well known that the concrete industry has to contribute to the sustainability of construction. For this intent it is necessary to reduce the cement content without compromising the durability requirements of the concrete constructions. Therefore, large scale cement replacement in concrete by by products such as fly ash will be extremely beneficial from the overall ecological and environmental point of view. In this context, an experimental research work was carried out focused on the evaluation of the possibility of producing low portland cement content concrete with enhanced or even high performances, including local by products such as fly ash and common low cost aggregates without any previous treatment, i. e., as received. Three different concrete mixtures (incorporating large quantities of fly ash) were made and their mechanical, workability and durability properties were characterized. The total binder used (400 kg/m3, 500 kg/m3 and 600 kg/m3) was composed by 40% of portland cement and 60% of fly ash by mass of the total cementitious material. The overall results obtained show that the compressive strength requirements, in general, are fulfilled and that these concretes are highly durable. Thus, by using this type of concrete it is possible to build more durable structures and contribute as well to the construction sustainability.